Ambiguity of Damages in Civil Court Decisions: A Case-Based Analysis of Racial and Ethnic Discrimination in Indonesia - Rusydi, Bustanul Arifien (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2024)
This study examines the ambiguity of damages in civil court decisions concerning racial and ethnic discrimination in Indonesia. Using a normative legal method with philosophical, conceptual, and case study approaches, the research focuses on the application of adequate causality theory by Johannes von Kries to assess the causal relationship between discriminatory acts and non-material harm. The study analyzes court decisions Surabaya District Court Decision No. 529/Pdt.G/2014/PN. Sby, Central Jakarta District Court Decisions No. 588/Pdt.G/2017/PN.Jkt.Pst and No. 13/Pdt.G/2018/PN.Jkt.Pst, which were declared inadmissible due to insufficient proof of harm. Findings reveal that current evidentiary standards are limited to material losses, leaving psychological harm—such as trauma, fear, and social stigma—unaddressed. This research proposes normative parameters for evaluating non-material damages, including psychological intensity, public exposure, duration of impact, and social vulnerability of victims. The study highlights the need for a more responsive evidentiary framework that accommodates the realities of symbolic and immaterial harm in discrimination cases.